Using eulerlets to model steady uniform flow past a circular cylinder. Issue 5 (2nd November 2018) - Chadwick, E.; Christian, J.; Chalasani, K.
ABSTRACT: Consider uniform, steady flow past a circular cylinder at Reynolds numbers 26, 36 and 40 before the flow becomes unsteady. Model the flow by using eulerlets, new Green's functions for Euler flow. This is the first time this eulerlet model has been used, introduced at the recent BETEQ 2017 International Conference. In addition, the far-field is also obtained by matching with oseenlets. Unlike existing Euler flow representations, the drag, wake eddies and far-field wake profile are all captured, and compare favourably with experiment.